Hubungan Kebersihan Gigi dan Mulut dengan Gingivitis pada Siswa Sekolah Dasar Kelas V Di Kabupaten Jember - Hestieyonini Hadnyanawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Oral hygiene determines by food debris, plaque, calculus, material alba, and stain at surface of tooth. The main cause of gingivitis is plaque, with following anomaly periodontal. The purpose of this study is to know the correlation of oral hygiene and gingivitis of class V (five) elementary school students in Kabupaten Jember. Method cross sectional was use in this study, and sample was taken by Stratified Random Sampling. Material and tools uses in this study are mouth glass, sonde, pincer, probe periodontal, sterile cotton, and alcohol 70%. The respondents examined and write OHI-S status and GI status. The result indicated that OHI-S status was relation with becomes gingivitis. Students with bad OHI-S status will become gingivitis (100%). This data was test by Chi square (X2), and indicated that there is correlation between oral hygiene and gingivitis (p = 0,000).